MODEL ADAPTASI EKOLOGIS DAN STRATEGI NAFKAH PADA MASYARAKAT SEKITAR TAMAN NASIONAL GUNUNG HALIMUN SALAK - rita rahmawati (Universitas Djuanda Bogor, 2011)
This research revealed an ecological adaptation and coping strategy of local community under conflict context between the community and government and the research took conflict case between local community and Halimun Salak Mountain National Park. Ultimate goal of the research was to recognize many factors affected community coping strategy and to design ecological adaptation model allowed community livelihood under wellbeing and maintained sustainable environment. Model of ecological adaptation and coping strategy formulated in the first year completed in the second year by including forest management policy and sustainable education. The model implemented with action research through natural resource management and livelihood environmental education for the local community and hopefully, the model will become an important media in positioning the local community in a significant role of forest manager and superintendent.